Traversable Finslerian wormholes supported by phantom energy - Singh, Ksh. Newton; Rahaman, Farook; Deb, Debabrata; Maurya, S. K. (Frontiers in Physics, 2023)
This paper supplements the article (Eur. Phys. J. C 76: 246, 2016) by extending few more new wormhole solutions in the background of Finslerian geometry. Here, we present six more solutions by considering (i) a linear equation of state (EoS) p_r=ω ρ and three different shape functions, (ii) a linear relationship between radial and tangential pressure as p_t=n p_r with two different redshift functions and (iii) a specific density profile with a linear EoS p_r=ω ρ. It is found that all these wormholes are violating NEC signifying that the throats are opened by exotic matters. Since the EoS parameters, ω or ω_r=p_r/ρ for all the solutions are <-1, the corresponding exotic matter is none other than the phantom energy. Further, the two solutions in Case (ii) are not asymptotically flat since _r → ∞ [b(r)/r] rightarrow 0. To make it asymptotically flat we matched it with the Schwarzschild vacuum.